Transarterial Embolization of Iatrogenic Cystic Artery Pseudoaneurysm - Proença, Ana Luísa (2019)
Cystic artery pseudoaneurysm (CAP) is a rare entity most often resulting from inflammatory conditions (acute cholecystitis or pancreatitis) or iatrogenic trauma (cholecystectomy). We report the case of a 73-year-old female who presented with abdominal pain and gastrointestinal bleeding after an episode of acute cholecystitis and endoscopic retrograde cholangiopancreatography for choledocolithiasis removal. Computed tomography and angiography revealed a CAP measuring 5 cm. A right hepatic artery transcatheter embolization was performed with glue, excluding the pseudoaneurysm. The next day, the patient underwent open cholecystectomy with ligation of the cystic artery. Later, ischemic hepatitis and abscess developed.